Gatekeeping in the Field: Strategies and Practices. Issue 2 (1st June 2016) - Freeman, Brenda J.; Garner, Curtis M.; Fairgrieve, Lori A.; Pitts, Michael E.
Abstract : Though counseling graduate programs often rely heavily on field site supervisors for help remediating interns with professional competence problems, there is little published research on the remediation and gatekeeping strategies used by field site supervisors. This article presents the results of a descriptive study of 103 field site supervisors on perspectives and strategies for gatekeeping and remediating counselors-in-training. The most common gatekeeping and remediation strategies reported by participants were consulting with other professionals, discussing the issue directly with the supervisee, and increasing live supervision. Only 35% reported discussing the student with counselor education faculty.